1978
DOI: 10.1530/jrf.0.0540209
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the histology of the testis of the red deer, Cervus elaphus

Abstract: Summary. A histological study of the testes of stags shot in autumn (sexual season) and spring (quiescent period) indicated that the 3-fold increase in testicular size observed in the autumn was accompanied by increases in nearly all features studied (volumes of intertubular tissue, Leydig cells, blood vessels and peritubular cells; diameter and length of seminiferous tubules ; the number of A1 spermatogonia and products of spermatogonial divisions, meiosis and spermiogenesis). There were, however, fewer A0 sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Based on our observations using the tubular morphology method, we identified and characterized eight distinct stages of seminiferous epithelium in this study. These findings are consistent with those described for many mammalian species reported previously, such as the brown brocket deer [ 3 ], red deer [ 7 ], landrace boar [ 10 ], roe deer [ 11 ], wild boar [ 12 ], and rusa deer (Cervus timorensis) [ 19 ]. In contrast to primates, for example, marmosets, two or more cellular associations (stages of seminiferous epithelium) were identified from a cross section of the seminiferous tubule [ 18 ], because spermatogenesis as in marmoset is asymmetrically distributed, resulting in more than one stage per cross section of seminiferous tubule [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Based on our observations using the tubular morphology method, we identified and characterized eight distinct stages of seminiferous epithelium in this study. These findings are consistent with those described for many mammalian species reported previously, such as the brown brocket deer [ 3 ], red deer [ 7 ], landrace boar [ 10 ], roe deer [ 11 ], wild boar [ 12 ], and rusa deer (Cervus timorensis) [ 19 ]. In contrast to primates, for example, marmosets, two or more cellular associations (stages of seminiferous epithelium) were identified from a cross section of the seminiferous tubule [ 18 ], because spermatogenesis as in marmoset is asymmetrically distributed, resulting in more than one stage per cross section of seminiferous tubule [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, the postmeiotic phase of the seminiferous epithelium was reported to be more frequent than the premeiotic and meiotic phases in donkeys and mules [ 9 ] and also in llamas (Lama glama) [ 23 ]. In red deer, there are no major differences among the relative frequency of all stages of the seminiferous epithelium, although during breeding season it was reported that the premeiotic phase had the highest frequency [ 7 ]. In other temperate deer such as roe deer, the complete stage of the spermatogenic cycle was found in the rutting period (May–August), but in the postrutting period (November) the seminiferous epithelium was aligned only by Sertoli cells and spermatogonia [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same endogenous circannual rhythm has been confirmed in red deer males, called stags, that show highly synchronized testicular cycles with a peak that overlaps the females' ovulation [5,9,10]. The almost complete suspension in spermatogenesis, during the non-rutting season (February-April), is further proof of such synchronization process [11]. Progesterone (P4) secreted by corpora lutea is necessary for the maintenance of pregnancy [12,13], while the contribution of placental progesterone is still to be assessed.…”
Section: Introductionmentioning
confidence: 62%
“…Based on the value of the STTL and the number of nucleoli of Sertoli cells (S) per seminiferous tubule, cross-sections were used to calculate the total number of Sertoli cells (NTSC) per testis using the formula described by Hochereau-de-Reviers and Lincoln 33 : NTSC = (STTL × nº corrected from S per transverse section)/thickness section. To determine the NTSC per gram of testis, the calculated NTSC was divided by the weight of the testis.…”
Section: Methodsmentioning
confidence: 99%